Salinity Stress Responses and Adaptation Mechanisms of Zygophyllum propinquum: A Comprehensive Study on Growth, Water Relations, Ion Balance, Photosynthesis, and Antioxidant Defense - Bilquees Gul; Sumaira Manzoor; Aysha Rasheed; Abdul Hameed; Muhammad Zaheer Ahmed; Hans-Werner Koyro (Plants)
Zygophyllum propinquum (Decne.) is a leaf succulent C4 perennial found in arid saline areas of southern Pakistan and neighboring countries, where it is utilized as herbal medicine. This study investigated how growth, water relations, ion content, chlorophyll fluorescence, and antioxidant system of Z. propinquum change as salinity levels increase (0, 150, 300, 600, and 900 mM NaCl). Salinity increments inhibited total plant fresh weight, whereas dry weight remained constant at moderate salinity and decreased at high salinity. Leaf area, succulence, and relative water content decreased as salinity increased. Similarly, the sap osmotic potential of both roots and shoots declined as NaCl concentrations increased. Except for a transitory increase in roots at 300 mM NaCl, sodium concentrations in roots and shoots increased constitutively to more than five times higher under saline conditions than in non-saline controls. Root potassium increased briefly at 300 mM NaCl but did not respond to NaCl treatments in the leaf. Photosynthetic pigments increased with 300 and 600 mM NaCl compared to non-saline treatments, although carotenoids appeared unaffected by NaCl treatments. Except for very high NaCl concentration (900 mM), salinity showed no significant effect on the maximum efficiency of photosystem II photochemistry (Fv/Fm). Light response curves demonstrated reduced absolute (ETR*) and maximum electron transport rates (ETRmax) for the 600 and 900 mM NaCl treatments. The alpha (α), which indicates the maximum yield of photosynthesis, decreased with increasing NaCl concentrations, reaching its lowest at 900 mM NaCl. Non-photochemical quenching (NPQ) values were significantly higher under 150 and 300 mM NaCl treatments than under non-saline and higher NaCl treatments. Electrolyte leakage, malondialdehyde (MDA), and hydrogen peroxide (H2O2) peaked only at 900 mM NaCl. Superoxide dismutase and glutathione reductase activities and glutathione content in both roots and shoots increased progressively with increasing salinity. Hence, growth reduction under low to moderate (150–600 mM NaCl) salinity appeared to be an induced response, while high (900 mM NaCl) salinity was injurious.